ANALISIS PERAN MEDIASI KOMITMEN ORGANISASI DAN PERSEPSI TERHADAP INOVASI DALAM HUBUNGAN PARTISIPASI ANGGARAN TERHADAP KINERJA MANAJERIAL - Ayu Ciptaningrum; Marsono Marsono (Diponegoro Journal of Accounting, 2026)
This study aims to examine the mediating role of organizational commitment and perception of innovation in the relationship between budgetary participation and managerial performance among echelon IV officials in vertical work units of the Directorate General of Treasury. This research employs a quantitative approach using Partial Least Squares Structural Equation Modeling with SmartPLS 3.0. The data were collected through questionnaires distributed to echelon IV officials who were actively involved in budgeting activities. A total of 113 responses were analyzed using bootstrapping procedures.The results show that budgetary participation has a positive and significant effect on managerial performance. In addition, organizational commitment and perception of innovation partially mediate the relationship between budgetary participation and managerial performance. These findings indicate that budgetary participation improves managerial performance not only directly, but also indirectly by strengthening organizational commitment and encouraging innovative perceptions among managers. The results imply that public sector organizations need to develop substantive budgetary participation mechanisms to improve managerial effectiveness, strengthen commitment, and foster an innovation-oriented work culture.